2019
DOI: 10.32602/jafas.2019.0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Tax, Tunneling Incentive, Bonus Mechanisms, And Firm Size On Transfer Pricing (Indonesian Evidence)

Abstract: Transfer pricing is the transaction price in the form of tangible goods, intangible goods or the provision of services between parties that have a special relationship. Transfer pricing used by companies in order to avoid tax payments that can cause problems for the tax authorities in their efforts to maximize revenue from the tax sector. This study aims to analyze the effect of taxes, tunneling incentives, bonus mechanisms, and firm size on transfer pricing in manufacturing sector. This study selected 28 manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 8 publications
2
23
1
6
Order By: Relevance
“…In the meantime, a study by (Yulia et al, 2019) investigating the international ownership relationship produced the opposite outcome. Research by Nazihah et al (2019) has revealed a positive impact on the bonus mechanism's transfer pricing decisions, which contrasts to Susanti & Firmansyah's study (2018). Merle et al (2019) research shows that debt covenant positively impacted the price of transfers, which is not consistent with Indrasti's study (2016).…”
Section: Introductioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In the meantime, a study by (Yulia et al, 2019) investigating the international ownership relationship produced the opposite outcome. Research by Nazihah et al (2019) has revealed a positive impact on the bonus mechanism's transfer pricing decisions, which contrasts to Susanti & Firmansyah's study (2018). Merle et al (2019) research shows that debt covenant positively impacted the price of transfers, which is not consistent with Indrasti's study (2016).…”
Section: Introductioncontrasting
confidence: 67%
“…A study from Tang (2016) found that tunneling incentives positively impact tax avoidance. This study is, however, inversely related to research by (Nazihah et al, 2019). Besides, Pratama (2020) found that corporate governance mechanism has a negative impact on transfer pricing.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Sementara itu, penelitian Nugroho et al, (2018) mendefinisikan firm size sebagai skala seberapa besar atau kecil suatu perusahaan yang dapat menunjukkan stabilitas, keseimbangan, dan kemampuan perusahaan dalam melakukan aktivitas ekonominya. Proksi pada penelitian ini sama dengan yang digunakan dalam penelitian Nugroho et al, (2018); Septiyani et al, (2018); dan Fuadah dan Nazihah (2019). Variabel firm size diukur menggunakan Log natural Total Assets.…”
Section: Firm Sizeunclassified